The Inspiration of God and Wolfhart Pannenberg's “Field Theory of Information” - Medley, George (2013)
This paper will examine the implications of an extended “field theory of information,” suggested by Wolfhart Pannenberg, specifically in the Christian understanding of creation. The paper argues that the Holy Spirit created the world as field, a concept from physics, and the creation is directed by the logos utilizing information. Taking into account more recent developments of information theory, the essay further suggests that present creation has a causal impact upon the information utilized in creation. In order to adequately address Pannenberg's hypothesis that the logos utilizes information at creation the essay will also include an introductory examination of Pannenberg's Christology which shifts from a strict “from below” Christology, to a more open “third way” of doing Christology beyond “above” and “below.” The essay concludes with a brief section relating the implications of an extended “field theory of information” to creative inspiration, as well as parallels with human inspiration.
Keywords: Pierre Teilhard de Chardin; John Polkinghorne; philosophy of science; Arthur Peacocke; Wolfhart Pannenberg; Information; Holy Spirit; field theory; Divine Action; Creation